Rural Amenity and Rural Change in Temperate Australia: Implications for Development and Sustainability - Argent, Neil; Tonts, Matthew; Jones, Roy; Holmes, John (Journal for Geography, 2009)
Many rural areas in the developed world are experiencing planning and development challenges related to processes of population change. The nature, direction and regional manifestations of these changes are strongly related to the varying levels of local amenity. These result from the qualities of the local social, economic and physical environments and contribute to the ability of rural regions to attract and retain residents. In turn the presence or absence of this attractive ability is likely to engender development and sustainability challenges related to growth, decline or (where the attractive forces are demographically specific) social mix. This paper considers these challenges in the context of high amenity rural regions in temperate Australia.